Risk assessment and persistence evaluation of Spiromesifen 240 SC on cucumber in India. (16th December 2019) - Banerjee, Tirthankar; Agyani, Manoj Kumar
Spiromesifen 240 SC was applied @ 144 g a.i./ha (T1) and 288 g a.i./ha (T2) on cucumber twice in ten days interval under randomised block designed field experiment. Cucumber fruit samples were collected at different day's interval, subjected to extraction and clean-up by modified QuEChERS technique and residue of spiromesifen was quantified by GC-ECD. Initial deposits of spiromesifen in cucumber fruit were 0.43 and 0.80 mg/kg for T1 and T2, respectively. No residue detected in harvest samples above LOQ. Half-life (t1/2 ) of spiromesifen were calculated 2.12 and 2.19 days and safe waiting period (TMRL ) were determined 5.83 and 8.11 days for T1 and T2, respectively. TMRC was much lesser than MPI even though initial deposit was considered. The % ADI values were 8.82% and 16.52% at highest residual deposits on 0 day for single and double dose respectively indicates safety for human consumption.